Effect of sodium silicate on chlorine content of palm oil - Jaganathan, Kiruba; Siti Nur Fairus, Azman; Zulfa Kurnia Umani, .; Syamsul Bahari, Abdullah; Che Rahmat, Che Mat; Mohd Sabri, Mahmud (AIP Publishing, 2025)
Chlorine content is a new quality control parameter for crude palm oil (CPO) due to food toxic contaminant concern. Current dechlorination using free-chlorine water washing needs improvement and using alkaline dechlorinating agent is one of the favorable, new options. This study aimed to investigate the effect of sodium hydroxide that is dissociated partially from sodium silicate (SS) aqueous on the chlorine content. Aqueous chlorine measured by spectroscopy meter indicates the amount of chlorine extracted from palm oil. Combustion ion chromatography was also used to check total chlorine content in palm oil. Dichloromethane in refined-bleached-deodorize palm oil (RBDPO) was employed to simulate organic chloride contaminant in CPO. The functional group and free fatty acids of palm oil were detected and measured by using FTIR. The SS solution at concentrations ranged from 0.1% to 1% were used for three molar ratios between RBDPO and SS: 1:1, 1:2 and 2:1. Two clear liquid layers were obtained from the liquid mixing. SS solution additions to CPO evidently increased presence of chloride in its aqueous phase indicating dechlorination had occurred. The highest chlorine content was achieved for 1:2 molar ratio and 1% SS concentration.